2003
DOI: 10.1046/j.1524-4725.2003.29107.x
|View full text |Cite
|
Sign up to set email alerts
|

Multiple Infundibulocystic Basal Cell Carcinomas: Case Report of Unique Unilateral Presentation

Abstract: A patient with clinically indolent multiple unilateral infundibulocystic basal cell carcinomas is described. Given the location of these multiple lesions, standard treatment modalities for basal cell carcinomas would have significant cosmetic and functional implications. A management approach with clinical follow-up and surgical intervention only for changing lesions is discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 20 publications
0
6
0
Order By: Relevance
“…Lesions strikingly similar to human basaloid follicular hamartoma (BFH) may develop . Human BFH has some common histopathological features with infundibulocystic BCC . The pits in our patient demonstrated basaloid buds emanating from the outer borders of the epidermal invaginations, but the BCCs removed were histopathologically variable, including nodular, infundibulocystic, pigmented, adenoid and superficial types.…”
Section: Discussionmentioning
confidence: 67%
“…Lesions strikingly similar to human basaloid follicular hamartoma (BFH) may develop . Human BFH has some common histopathological features with infundibulocystic BCC . The pits in our patient demonstrated basaloid buds emanating from the outer borders of the epidermal invaginations, but the BCCs removed were histopathologically variable, including nodular, infundibulocystic, pigmented, adenoid and superficial types.…”
Section: Discussionmentioning
confidence: 67%
“…Herman et al. 6 described multiple IBCCs with unique unilateral presentation on the face and one of our patients (patient 1) also had all the lesions confined to the right side of the body. The biological behaviour of IBCC seems to be less aggressive than that of other clinicopathological variants of BCC because most of the lesions remain small for a long time and show little tendency to ulcerate the epidermis 5…”
mentioning
confidence: 49%
“…IBCC is an uncommon variant of BCC and may be found as a sporadic lesion, or as a hereditary syndrome. The recent 5–7 and present reports have shown that patients may have multiple or even more than 100 lesions. The site of predilection is the face but the lesions could be seen on the scalp, neck, trunk, extremities and vulva 1,5–9 .…”
mentioning
confidence: 67%
“…To our knowledge, there have been five reports of such cases, two of which reported three pedigrees in sum total of multiple hereditary IBCC 10,11 . The other three reports are of multiple IBCC, either located on the face of a person infected with the human immunodeficiency virus, 12 around the mouth with a unilateral presentation, 13 or over the lines of Blaschko 14 …”
Section: Discussionmentioning
confidence: 99%